Seasonal Variability of Volatile Components in Calypogeia integristipula - Wawrzyniak, Rafał; Guzowska, Małgorzata; Wasiak, Wiesław; Jasiewicz, Beata; Bączkiewicz, Alina; Buczkowska, Katarzyna (Molecules (Basel, Switzerland), 2023)
Liverworts contain a large number of biologically active compounds that are synthesised and stored in their oil bodies. However, knowledge about the chemical composition of individual species is still incomplete. The subject of the study was Calypogeia integristipula, a species representing leafy liverworts. Plant material for chemotaxonomic studies was collected from various locations in Poland. The chemical composition was determined in 74 samples collected from the natural environment in 2021 and 2022 in three growing seasons: spring, summer and autumn, and for comparison with samples originating from in vitro culture. The plants were classified as Calypogeia integristipula on the basis of morphological characteristics, oil bodies, and DNA markers. The volatile organic compounds (VOCs) from the biological material were extracted by headspace solid phase microextraction (HS-SPME). The samples were then analysed by gas chromatography–mass spectrometry (GC-MS). A total of 79 compounds were detected, of which 44 compounds were identified. The remaining compounds were described using the MS fragmentation spectrum. Cyclical changes in the composition of compounds associated with the growing season of Calypogeia integristipula were observed. Moreover, samples from in vitro culture and samples taken from the natural environment were shown to differ in the composition of chemical compounds. In terms of quantity, among the volatile compounds, compounds belonging to the sesquiterpene group (46.54–71.19%) and sesqiuterpenoid (8.12–22.11%) dominate. A smaller number of compounds belong to aromatic compounds (2.30–10.96%), monoterpenes (0.01–0.07%), monoterpenoids (0.02–0.33%), and aliphatic hydrocarbons (1.11–6.12%). The dominant compounds in the analysed liverworts were: anastreptene (15.27–31.14%); bicyclogermacrene (6.99–18.09%), 4,5,9,10-dehydro-isolongifolene (2.00–8.72%), palustrol (4.95–9.94%), spathulenol (0.44–5.11%).